Integrating Islamic Values and Indigenous Psychology in Character Education: A Contextual Approach to Adolescent Moral Development in Madrasahs - Muhammad Farhan; Ali Mustofa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Character education is essential for developing adolescents with integrity, morality, and global competitiveness, particularly within Indonesia's multicultural and religious context where Islamic values and local wisdom remain highly relevant in addressing contemporary moral challenges. However, rapid digitalization, globalization, and the influence of social media have contributed to declining empathy, moral confusion, and identity crises among youth, while conventional character education in madrasahs often fails to address students' psychological and cultural contexts effectively. In response to these challenges, the integration of Islamic values with indigenous psychology offers a culturally sensitive and holistic framework for character development by combining Islamic moral principles with local cultural understanding. This integrative approach has the potential to create more authentic, relevant, and effective character education programs that align with both the religious and cultural identities of students. This study aims to examine the integration of Islamic values and indigenous psychology in character education through comprehensive literature analysis and case study examination. The research addresses three primary questions: (1) How can Islamic values and indigenous psychology be theoretically integrated in character education frameworks? (2) What are the practical implementations, successes, and challenges of this integration in madrasah settings? (3) What impacts can be expected from this integrative approach on adolescent moral development, and what are the implications for future practice? This study employed a qualitative research approach using systematic literature review methodology combined with illustrative case study analysis. The systematic literature review design was chosen to provide comprehensive understanding of theoretical frameworks, while case studies offered practical insights into implementation experiences. This mixed-method approach enables both theoretical synthesis and practical application analysis. Data analysis employed thematic content analysis following systematic review protocols with NVivo 12 software support for coding management and theme identification. The analysis process involved four stages: (1) initial coding of relevant concepts from each source using open coding techniques, (2) thematic categorization of codes into broader conceptual themes through axial coding, (3) synthesis of findings to identify patterns and relationships via selective coding, and (4) development of integrative framework based on synthesized themes. Two independent researchers conducted initial coding to ensure inter-rater reliability, achieving Cohen's kappa coefficient of 0.83, indicating substantial agreement. Discrepancies were resolved through discussion and consensus-building. For case study analysis, multiple data sources were utilized including institutional documents, interview transcripts with administrators and teachers, and observational notes. Triangulation techniques were employed through multiple data sources (documentary evidence, interviews, observations), multiple perspectives (administrators, teachers, students), and member checking with participants to validate findings. Cross-case analysis identified common patterns and unique contextual factors influencing implementation success, ensuring both within-case depth and cross-case generalizability. Findings reveal significant theoretical convergence between Islamic moral principles and indigenous psychological concepts. Key convergence areas include community-centered moral development, holistic human understanding, and exemplary figure roles in character formation. Case studies from two madrasahs demonstrate practical implementation through contextual learning approaches, experiential programs, and reflective practices, though challenges exist in teacher preparation and resource allocation. The research proposes a contextualized model of moral education that synergizes both paradigms to address contemporary character challenges while maintaining cultural authenticity and religious integrity. The integration represents a promising approach for enhancing character education effectiveness in madrasah settings.